A high-throughput micropatterning platform for screening of nanoparticles in regenerative engineering - Koh, Cheryl Jie Yan (2023)
Engineered nanoparticles (ENPs) have been gaining traction in the field of regenerative engineering due to their unique physical, chemical and biological properties that are able to modulate cellular behaviour by influencing cell adhesion, migration, and proliferation. These nanomaterial-cellular interactions are important in directing tissue regeneration processes at the cellular level. However, the usage of nanoparticles brings about safety concerns with regards to impairment of cellular dynamics. In this context, micropatterning platform has emerged as a high-throughput tool for assessing stress response of ENPs. This platform not only allow the analysis of biological responses to nanoparticles in a controlled and reproducible environment, but also provides the identification of subtle effects that may not be discernible using traditional methods. This abstract discusses how two commonly incorporated engineered nanoparticles in regenerative engineering, specifically zinc oxide (ZnO) and titanium dioxide (TiO2) have an influence on collective epithelial rotation via the use of micropatterned platform. The confinement of cells in geometrical constraints were achievable through the precise control over the geometry and size of the adhesive fibronectin islands which aids in cell attachment. Collective rotation is essential in tissue morphogenesis and wound healing, and disruption to this collective behaviour could lead to a wide range of biological dysregulations. Through this approach, it was observed that the micropatterned human keratinocytes clusters exhibited spontaneous rotation without external stimulus, at relatively constant uniform speeds of 10 μm/h. However, acute (6 h) exposure to non-cytotoxic doses of ZnO and TiO2 NPs (≤100 nm) resulted in a loss of directionality and slowing down of cell rotation, respectively. The loss in collective cell rotation (CCR) was determined to be attributed to reactive oxygen species (ROS)-induced proliferation by ZnO. While cell proliferation is desired in regenerative engineering, the generation of new, heterogeneous localised velocity fields by the increased cell density led to cell jamming within the epithelial units. On the other hand, the retardation of the velocity of TiO2-treated units was most likely as a result of degradation of membrane recycling integrins that are necessary for continued cell migration. This is because TiO2-treated units were found to induce autophagy, which has been reported to compete with endocytosis- driven recycling. Taken together, our findings offer nano-biological insights into the distinct signalling pathways exerted by different nanoparticles - ZnO NPs promoting cell proliferation, yet disrupting cell migration, and TiO2 NPs decreasing cell migration. This suggests that when it comes to the usage of ENPs in regenerative engineering, further studies have to be done to ensure that cellular dynamics are not compromised.